(untitled) (Journal of Economic Research & Business Administration, 2016)
Waste management is the process of treating solid wastes and of-fers variety of solutions for recycling items that don’t belong to trash. It is about how garbage can be used as a valuable resource. Waste manage-ment is something that each and every household and business owner in the world needs and now as a part of sustainable development it takes an important place in every country’s sustainable development strategy. The article discusses the sustainable development policy of Singapore, its main directions and principles, and the current situation of waste management as a part of sustainable development policy. According to the National En-vironmental Agency of Singapore conducted a static analysis of the degree of waste and recycling rate in the country